Looking for compensation at multiple scales in a wetland bird community. Issue 6 (2nd June 2022) - Barraquand, Frédéric; Picoche, Coralie; Aluome, Christelle; Carassou, Laure; Feigné, Claude
Abstract: Compensatory dynamics, during which community composition shifts despite a near‐constant total community size, are usually rare: Synchronous dynamics prevail in natural communities. This is a puzzle for ecologists, because of the key role of compensation in explaining the relation between biodiversity and ecosystem functioning. However, most studies so far have considered compensation in either plants or planktonic organisms, so that evidence for the generality of such synchrony is limited. Here, we extend analyses of community‐level synchrony to wetland birds. We analyze a 35‐year monthly survey of a community where we suspected that compensation might occur due to potential competition and changes in water levels, favoring birds with different habitat preferences. We perform both year‐to‐year analyses by season, using a compensation/synchrony index, and multiscale analyses using a wavelet‐based measure, which allows for both scale‐ and time‐dependence. We analyze synchrony both within and between guilds, with guilds defined either as tightknit phylogenetic groups or as larger functional groups. We find that abundance and biomass compensation are rare, likely due to the synchronizing influence of climate (and other drivers) on birds, even after considering several temporal scales of covariation (during either cold or warm seasons, above or below the annual scale). Negative covariation in abundance at the guild or community level did only appear at the scale of a few months or several years. We also found that synchrony varies with taxonomic and functional scale: The rare cases where compensation appeared consistently in year‐to‐year analyses were between rather than within functional groups. Our results suggest that abundance compensation may have more potential to emerge between broad functional groups rather than between species, and at relatively long temporal scales (multiple years for vertebrates), above that of the dominant synchronizing driver. Abstract : While abundance compensation is key to explain the increased stability of communities relative to populations, it is rarely found in field data. Using a long‐term wetland bird community survey, we show that while synchrony dominates at most scales, compensation can be found between rather than within functional groups in the winter season, and at long temporal scales. This suggests that zooming out functionally and temporally may help in finding compensation in community time series.